The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1530/eje-08-0756
|View full text |Cite
|
Sign up to set email alerts
|

Glycodelin in reproductive endocrinology and hormone-related cancer

Abstract: Glycodelin is an endocrine-regulated glycoprotein that has significant effects on immune cells, apoptosis, reproduction, cell adhesion, differentiation and cancer. In reproduction, glycodelin contributes to capacitation and immunoprotection of spermatozoa, and it modulates sperm-oocyte binding, acrosome reaction and implantation. In endocrine-related cancer, the differentiation inducing effects of glycodelin are accompanied by growth restriction of malignant cells, decreased expression of oncogenes, increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 111 publications
(79 reference statements)
2
45
0
1
Order By: Relevance
“…To date, the expression of glycodelin has been well described mainly in hormone-related tumors such as breast and ovarian cancer (15). Zadran and colleagues (27) recently reported that glycodelin mRNA (PAEP) was one of the most differentially regulated genes in a small cohort of lung ADC patients compared with healthy patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the expression of glycodelin has been well described mainly in hormone-related tumors such as breast and ovarian cancer (15). Zadran and colleagues (27) recently reported that glycodelin mRNA (PAEP) was one of the most differentially regulated genes in a small cohort of lung ADC patients compared with healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Glycodelin A, the immunosuppressive form of glycodelin, functions as a proliferation-suppressor and apoptosis inducer of T cells, monocytes, B cells and NK cells (14). Atypical glycodelin expression is observed in hormone-related breast cancer, endometrial cancer, and ovarian cancer (15). Recent studies have demonstrated glycodelin expression in melanoma cells and lung cancer (16,17).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated to be important in a number of physiological processes, such as embryonic implantation, immunotolerance, contraception and gland differentiation. In recent years, several studies have demonstrated that PAEP is abnormally expressed in various types of tumors, such as endometrial carcinoma, ovarian cancer, breast cancer (2)(3)(4)(5), lung cancer (6) and melanoma (7). Transfection of PAEP cDNA into the MCF-7 breast cancer cell line results in marked changes in cell growth behavior, with the suppression of proliferation and formation of acinar structures (8), suggesting that PAEP inhibits tumor cell growth and promotes cell differentiation as a tumor suppressive factor.…”
Section: Introductionmentioning
confidence: 99%
“…Different glycoforms of glycodelin play important roles in regulation of sperm function [3]. Furthermore, glycodelin has immunosuppressive properties, which are thought to protect foetal semiallograft from maternal immune response [4,5].…”
Section: Introductionmentioning
confidence: 99%